The production of lymphokines by primary alloreactive T-cell clones: a co-ordinate analysis of 233 clones in seven lymphokine assays. - Sanderson, C J (1985)
A total of 233 primary alloreactive T-cell clones have been tested for the production of interleukin-2 (IL-2), interleukin-3 (IL-3), immune(gamma) interferon (IFN) and granulocyte-macrophage colony-stimulating factor (CSF-2), B-cell growth factor I and II (BCGFI, BCGFII), and eosinophil differentiation factor (EDF). EDF was assayed by means of the eosinophil differentiation assay (EDA). Two principal correlations were observed: IL-3 was shown to be the major lymphokine detected in the bone marrow proliferation assay (BMPA) used to detect CSF-2, and there was a high correlation between the EDA and BCGFII. Subsequent work has suggested that this latter correlation is because a single factor is responsible for both activities. Apart from these two exceptions, and low level correlations probably due to the fact that different assays detect more than one lymphokine, there was no evidence for co-ordinate expression of lymphokines. There was a large variation in amounts of individual lymphokines produced. More clones produced multiple lymphokines than would be expected from independent control. Taken together, this pattern of regulation is consistent with the hypothesis that antigen stimulation of T cells results in the activation of all the lymphokine genes, but the amount of each produced is determined by secondary controlling mechanisms.